2008
DOI: 10.1002/jssc.200800142
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mobile phase, ion pairing, and temperature influence on an HILIC‐MS/MS method for L‐arginine and its dimethylated derivatives detection

Abstract: Asymmetric N(G),-N(G)-dimethylarginine (ADMA) increases in diseases such as renal failure, diabetes mellitus, and hypercholesterolemia. The feasibility and utility of a hydrophilic interaction chromatography (HILIC) method for the separation of free L-arginine (Arg), ADMA, and symmetric N(G),-N(G')-dimethylarginine (SDMA) on a typical silica column were explored and the impact of some experimental parameters on the chromatographic behavior of these analytes was investigated. The effect of water and TFA content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 23 publications
2
19
0
1
Order By: Relevance
“…A similar drastic change of the retention time was observed when increasing the trifluoroacetic acid (TFA) percentage in the mobile phase [20], which suggested that strong negative charges might interfere with the HILIC mechanism.…”
Section: Pretreatment Of a Hydrolyzed Sample Solution Using An Anion supporting
confidence: 50%
“…A similar drastic change of the retention time was observed when increasing the trifluoroacetic acid (TFA) percentage in the mobile phase [20], which suggested that strong negative charges might interfere with the HILIC mechanism.…”
Section: Pretreatment Of a Hydrolyzed Sample Solution Using An Anion supporting
confidence: 50%
“…However, ARG, ADMA and SDMA are suitable analytes for the nowadays well established hydrophilic interaction (HILIC) chromatography [16], which is performed on a polar stationary phase with a mobile phase rich in organic modifier. As it turned out, a certain amount of trifluoroacetic acid in the mobile phase was necessary to produce tailing free peaks of the analytes [17]. Since it is well known that trifluoroacetic acid in the mobile phase causes signal suppression in an ESI ion source, a weaker acid (in this case propionic acid) had to be added in excess of the trifluoroacetic acid to alleviate this effect [18].…”
Section: Chromatography and Detectionmentioning
confidence: 99%
“…Column temperature is an important factor in HILIC separations [27][28][29] as it influences significantly on the following properties: (i) diffusivity of the analytes; (ii) viscosity of the MP, which is closely correlated with hydrophobicity and hydrophilicity of the MP; (iii) enthalpy and entropy change of the analytes in the transferring process from the MP to SP; (iv) pKa of the analytes and pH of the MP [30][31][32]. An increasing number of reports [18][19][20]25,[27][28][29]31,[33][34][35][36][37] on thermodynamics in HILIC were found in recent years, which provided necessary theory guidance when column temperature was used as a variant regulating selectivity and analysis speed.…”
Section: Effect Of Column Temperaturementioning
confidence: 99%